Effectiveness of Chicken Manure Flower Extract (Tagetes ercta L.) Against Mortality and Antifeedant in Chili Aphid Pests Myzus persicae sulz - Hotni Doani Purba; Helen J. Lawalata; Utari Satiman; Aser Yalindua; Christny F. E. Rompas (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
This research was motivated by the chicken dung flower plant (Tagetes erecta L.) which is one of the plants that is often found in several areas in North Sulawesi, containing active chemical compounds such as alkaloids, terpenoids, saponins, tannins and flavonoids which can improve health. improve health. improve health. improve health. improve health. improve health. used as a vegetable protector. This study aims to determine the effectiveness of chicken manure flower extract on the mortality and antifeedant effect of chili aphids Myzus persicae sulz. This examination utilized an exploratory technique utilizing the leaf separate strategy utilizing a Totally Randomized Plan (CRD) design comprising of 4 treatments and 4 replications. Each treatment was given chicken manure flower extract with respective concentrations, namely P0 (0%), P1 (5%), P2 (10%), and P3 (15%). The results showed that the administration of chicken manure flower extract had a significant effect on the death of the chili aphid Myzus persicae sulz. The higher the extract from chicken manure flowers the higher the death rate of chili aphids Myzus persicae sulz and chicken manure flowers have an antifeedant effect at a concentration of 15%. So it can be concluded that giving chicken manure flower extract is effective in increasing the mortality of Myzus persicae sulz at a concentration of 15%, namely an average of 4.75 birds and has an antifeedant effect at a concentration of 15.%, namely an average of 0.350 grams.